Interpersonal Meaning In Donald Trump’s Speech In Response To Coronavirus Pandemic - Vivi Heryanti Damanik; T. Thyrhaya Zein; Nurlela Nurlela (Jurnal Sains Sosio Humaniora, 2020)
This research is to examine the use of Mood and Speech Function in Donald Trump's speech in response coronavirus pandemic. The rise of the coronavirus pandemic that occurred in almost all parts of the world in December 2019 - 2020 which has not yet ended, made America the largest country affected by the coronavirus pandemic after Italy. This thing has made Donald Trump speaking out in an effort to stop the spread of the coronavirus in America. The analysis of this research based on Eggins (2004:14) which includes Realization of Speech Function in mood system. This paper concerns on the analysis of Mood and Speech Function in Donald Trump’s speech in response coronavirus pandemic. This uses descriptive research method, in which the data are described systematically to get an accurate and factual result. The data used in this study are the clauses containing of grammatical mood and speech function used by Donald Trump’s speech. The finding describes that as a president want to give his response to the spread of this global pandemic. Where the response is in the form of information and opinions carried out in preventing the spread of the coronavirus pandemic to the citizens of America. It also to analyze how the mood and speech function realized in Donald Trump’s speech.